Employee Performance in A Rural Bank: The Effects of Work–Life Balance, Workload, And Self-Efficacy (Case of PT Bank Perekonomian Rakyat Desa Sanur, Bali) - Putra, I Kadek Arya Dwi Prayana; Puspitawati, Ni Made Dwi; Parwita, Gde Bayu Surya (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Employee performance plays a key role in determining an organization's success in achieving its goals. Specifically, optimal performance demonstrates the ability, responsibility, and dedication of workers in carrying out their duties based on industry standards. However, at PT. Bank Perekonomian Desa Sanur, employee performance has declined and fluctuated. This can be seen from the unstable achievement of targets. This condition is thought to be caused by factors such as work-life balance, workload, and employee self-efficacy. Therefore, this study aims to examine the influence of work-life balance, workload, and self-efficacy on employee performance at PT. Bank Perekonomian Desa Sanur. The data collection methods used in this study include interviews, observation, documentation, and questionnaires. The approach applied is quantitative using multiple linear regression, which is analyzed through SPSS. The population of this study includes all employees of PT. Bank Perkekonomian Desa Sanur, with a sample of 35 respondents obtained through a saturated sampling technique. The results of the study state that work-life balance has a positive and significant effect on employee performance. This means that the better the balance between personal life and work, the better the employee performance. On the other hand, workload has a negative and significant effect. This means that the higher the workload felt by workers, the lower their performance. Self-efficacy shows a positive and significant effect. The findings confirm that the higher the level of self-efficacy in employees, the better their performance.